A linguagem do Douro em duas gerações de escritores: João de Araújo Correira e Camilo de Araújo Correia - Santana, Maria Olinda Rodrigues; Gouveia, Sofia; Borges, António José (Douro : Estudos & Documentos, 2022)
.